The Restricted Ovulator Chicken: A Unique Animal Model for Investigating the Etiology of Ovarian Cancer. Issue 5 (1st June 2010) - Giles, James R.; Elkin, Robert G.; Trevino, Lindsey S.; Urick, Mary E.; Ramachandran, Ramesh; Johnson, Patricia A.
Abstract : Objective: The main goal of this study was to compare the incidence of ovarian cancer (OC) in 2 genetically different lines of hens-one that generally fails to lay eggs (the mutant "restricted ovulator" [RO] strain) and the other consisting of the wild-type (WT) siblings of the mutant RO hens. Methods: Individual egg production data were obtained over a 972-day period for 31 RO hens and 33 WT hens. At 38 months of age, hens were killed, and their abdominal cavities were examined for any gross evidence of tumors. Samples of ovarian tissue were processed and assessed for histopathology and protein expression of ovalbumin. Plasma estradiol concentrations were also determined. Results: Only 1 (3%) of the 31 RO hens was diagnosed with OC as compared with 9 (27%) of the 33 WT hens ( P < 0.05). Wild-type hens laid more eggs than did RO hens during the 31-month collection period (average of 422 vs 28, respectively; P < 0.05). Although there was no difference in overall rate of ovulation between hens with and without OC, WT hens diagnosed with OC laid a greater percentage of their total number of eggs in the first year of production. Plasma estradiol concentrations were higher ( P < 0.01) in RO versus WT hens. Conclusions: The results of this study strongly suggest that the number of ovulatory events is directly related to the incidence of OC in chickens. Clearly, other factors modify the risk of OC because there was no difference in ovulation rate between WT hens with and without OC. The mutant RO hen represents a valuable animal model for studying the etiology of OC.